Effect of rocuronium compared with succinylcholine on intraocular pressure during rapid sequence induction of anaesthesia. - Chiu, C.L.; Jaais, F.; Wang, C.Y. (Oxford University Press, 1999)
We have compared the effect of rocuronium and succinylcholine on intraocular pressure (IOP) during rapid sequence induction of anaesthesia using propofol and fentanyl, in a randomized double-blind study. We studied 30 adult patients, allocated to one of two groups. Anaesthesia was induced with fentanyl 2 micrograms kg-1 and propofol until loss of verbal response. This was followed by succinylcholine 1.5 mg kg-1 (group S; n = 15) or rocuronium 0.9 mg kg-1 (group R; n = 15). Laryngoscopy was performed 60 s later. IOP, mean arterial pressure (MAP) and heart rate (HR) were measured before induction, immediately before intubation and every minute after intubation for 5 min. A Keeler Pulsair air impulse tonometer was used to measure IOP and the mean of two readings obtained in the right eye at each measurement time was recorded. Intubating conditions were evaluated according to a simple scoring system. IOP in the succinylcholine group was significantly greater than that in the rocuronium group (mean 21.6 (SEM 1.4) mm Hg vs 13.3 (1.4) mm Hg; P < 0.001). Intubating conditions were equally good in both groups. We conclude that with rapid sequence induction of anaesthesia using propofol and fentanyl, rocuronium did not cause as great an increase in IOP as succinylcholine and may be an alternative in open eye injury cases.